Utilization of postnatal care services among mothers aged 15-24 years at Kisenyi Health Centre IV, Kampala City- a cross-sectional study. - Nantale , Esther; Nansereko, Hasifa; Nalubega, Jane Frank; Naggulu Posperia, Immaculate (Student’s Journal of Health Research Africa, 2025)
Background Postnatal care (PNC) is a critical component of maternal and newborn health, particularly during the first six weeks after delivery when the risk of complications is highest. Despite its importance, the utilization of PNC services remains low among young mothers in Uganda. This study aimed to assess the utilization of postnatal care services and associated factors among mothers aged 15–24 years who attended Kisenyi Health Centre IV in Kampala City. Methodology A descriptive cross-sectional study was conducted using a structured, self-administered questionnaire. A total of 42 mothers aged 15–24 years were selected through convenience sampling. Data were collected on participants’ background characteristics, knowledge, behaviors, and experiences with postnatal care services. Descriptive statistics were used to analyze the data, and results were presented in frequencies, percentages, and tables. Results The majority of respondents (52.4%) were aged 15–19 years, and 33.3% had attained secondary education. Most participants (66.7%) resided in urban areas, and 54.8% were unemployed. While 97.6% reported that PNC services were available at the facility, only 23.8% had a birth plan, and 31.0% rated their knowledge of PNC as poor. Health workers were the primary source of PNC information (50.0%), and 42.9% of respondents visited the clinic three times or more. Factors such as distance to the facility, perceived quality of care, provider attitudes, and affordability influenced utilization. Conclusion Despite the high availability of PNC services at Kisenyi HC IV, limited knowledge, lack of birth preparedness, and mixed perceptions of care quality still hindered their utilization by young mothers. Recommendations Health education during antenatal care, promoting respectful and youth-friendly services, should be enhanced. Increase community outreach to improve awareness and accessibility of PNC among adolescents and young mothers.